Solar light driven dye degradation using novel organo–inorganic (6, 13-pentacenequinone/TiO2) nanocomposite1. Issue 14 (19th February 2015) - Pandit, Vikram U.; Arbuj, Sudhir S.; Pandit, Yashwant B.; Naik, Sonali D.; Rane, Sunit B.; Mulik, Uttam P.; Gosavi, Suresh W.; Kale, Bharat B.
<x xml:space="preserve">Abstract</x> The 6, 13-pentacenequinone loaded TiO2 catalyst was successfully synthesized via simple wet-impregnation. The highest apparent rate constant was observed among the prepared catalysts is 5.2 × 10−2 min−1 using a PQ/TiO2 catalyst having 0.2 wt% PQ.